(untitled)
This paper contributes to the policy discussion on Covid-19 by presenting real-time evidence on the magnitude of the shock for Italian firms. We take advantage of unique panel data on 7,800 companies between January 2020 right before the pandemic and March of the same year in the midst of lockdown policies. We then exploit the revision in expectation within this short time window to capture the impact of firms' idiosyncratic shock. Our analysis shows disproportionate effects for internationalized companies and provide some evidence on supply chain contagion. We also document stronger shocks for truly innovative companies and effects on long-run growth operating through the disruption of preexisting R&D plans., address = Essen, author = Emanuele Brancati and Raffaele Brancati, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = D84; F00; O3; 330; Covid-19; Firms; Expectations; Internationalization; Innovation; Global Value Chains, language = eng, number = 649, publisher = Global Labor Organization (GLO), title = Heterogeneous Shocks in the Covid-19 Pandemic: Panel Evidence from Italian Firms, type = GLO Discussion Paper, url = https://hdl.handle.net/10419/223312, year = 2020